Integrasi PjBL dan Isu Lingkungan: Upaya Meningkatkan HOTS dan Keterampilan Proses dalam Pembelajaran Fisika SMA - Masyithah, Nafa; Hariyono, Eko (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Global warming is a global environmental issue that demands the integration of authentic issues into science learning. In physics education, an approach is needed that not only conveys concepts, but also develops students' Higher Order Thinking Skills (HOTS) and science process skills. This study aims to analyze the effect of the Project-Based Learning (PjBL) model based on global warming issues on improving students' HOTS and science process skills at the high school level. The method used is a quasi-experimental design with a non-equivalent control group. The sample consisted of 70 grade 10 students selected through a purposive sampling technique, divided into experimental and control groups. The research instruments were essay tests based on the revised Bloom's taxonomy to measure HOTS and science process skills observation sheets. Data analysis was carried out using an independent sample t-test and N-gain calculation using SPSS. The results showed a significant difference between the experimental and control groups (p = 0.000 < 0.05), with an average N-gain of the experimental group of 0.640 (moderate category). These findings indicate that the PjBL model, which integrates environmental issues, is effective in improving students' higher-order thinking skills and science process skills. These findings imply the need for contextually relevant project-based learning to equip students with 21st-century competencies, particularly in addressing global issues such as climate change.